menu
QAmmunity.org
Login
Register
My account
Edit my Profile
Private messages
My favorites
Register
Ask a Question
Questions
Unanswered
Tags
Categories
Ask a Question
Find (f-g)(x) when f(x)=3x+2 g(x)=2x^2-4 h(x)=x^2-x+7
asked
Mar 14, 2022
91.5k
views
13
votes
Find (f-g)(x) when f(x)=3x+2 g(x)=2x^2-4 h(x)=x^2-x+7
Mathematics
high-school
Martin Kool
asked
by
Martin Kool
5.1k
points
answer
comment
share this
share
0 Comments
Please
log in
or
register
to add a comment.
Please
log in
or
register
to answer this question.
1
Answer
3
votes
(f + g)(x) = f (x) + g(x)
= [3x + 2] + [4 – 5x]
= 3x + 2 + 4 – 5x
= 3x – 5x + 2 + 4
= –2x + 6
Marlea
answered
Mar 19, 2022
by
Marlea
4.8k
points
ask related question
comment
share this
0 Comments
Please
log in
or
register
to add a comment.
Ask a Question
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.
5.2m
questions
6.8m
answers
Other Questions
Pizza planet is running a special 3 pizzas for 16.50. What is the unit rate for one pizza
What number is halfway between 0 and 18
I need to simplify this expression.
Need answer to math problem!!!
Which property is shown in the problem below? -8(x-3y-9) = -8x+24y+72 A the associative property B the commutative property C the distributive property D the division property ASAP
Twitter
WhatsApp
Facebook
Reddit
LinkedIn
Email
Link Copied!
Copy
Search QAmmunity.org